Difficulties for FELTE English translation-majored students in approaching financial and banking terminology in the book “English for Finance and Banking” by Assoc.Prof.Dr. Nguyen Xuan Thom: causes and possible solutions = Khó khăn với sinh viên chuyên ngành Dịch trong việc tiếp cận thuật ngữ Tài chính Ngân hàng trong khóa học “Tiếng Anh Tài chính Ngân hàng”: Nguyên nhân và giải pháp đề ra - Đậu, Quốc Khánh (2021)
The present study aimed at figuring out the difficulties facing translation-majored students in approaching terminology in the “English for Finance and Banking” course. It also investigated the causes for the difficulties and possible solutions to overcome these difficulties. The finding of this study was based on analysis and discussions of the survey questionnaires and data collected from interviews. Overall, the results suggested that understanding terms causes the most trouble, and the major reason is in the students’ poor economic background and insufficient home revision. Many solutions have been proposed, including efforts from both students attending the course as well as the teachers, among which widening background knowledge and learning in groups were most suggested.